Mechanism of Electroacupuncture Quchi (LI 11) -Yanglingquan (GB 34) in Rats with Spasticity of Cerebral Apoplexy - Bin GUO; Penghan WANG; Linxing HUANG; Zhiqiang XIE; Lina XIE; Weiai LIU; Lizhen YI; Xin LIU; Zenghui YUE (康复学报)
Objective:The purpose of this study is to analyze the effects of electroacupuncture Quchi (LI 11) -Yanglingquan (GB 34) in Sprague-Dawley (SD) rats with spasticity of cerebral apoplexy (SCA) on the nerve injury, ultrastructural changes in synapses, and brain derived neurotrophic factor (BDNF), tyrosine protein kinase B (TrkB) and receptor gene expression levels in hippocampus, so as to reveal the efficacy and mechanism of electroacupuncture.Methods:A total of thirty-six SD rats were randomly divided into electroacupuncture group, sham operation group, model group and blank group, with nine SD rats in each group. A rat model of stroke and limb paralysis was prepared by modified Zea-Longa suture method and internal capsule injection of NMDA receptor method. The behavioral scoring confirmation model was followed by electroacupuncture treatment for five days. The ultrastructural changes of synapses in hippocampus were observed by electron microscopy. The expressions of BDNF and TrkB related genes in hippocampus were detected by RT-PCR. The expression of BDNF and TrkB protein in hippocampus was detected by Western blot.Results:(1) The neurological scores and Ashworth assessment of muscle tension in the model group were significantly higher compared with those in the blank group and the sham operation group respectively (P<0.01). Compared with the model group, the neurological scores and Ashworth assessment of muscle tension in the electroacupuncture group were statistically significant (P<0.05). (2) The number of synapses in the model group was significantly reduced and the anterior and posterior membranes and gaps were blurred. Besides, the number of synaptic vesicles was significantly reduced, the density uneven, the terminal cytoplasm of the postsynaptic cells severely damaged, and the dense density of postsynaptic bands decreased; The electroacupuncture group was denser than the model group, and the synaptic shape was closer to the sham operation group. The number of synaptic vesicles, the concave synapses increased, while the post-synaptic cell terminal cytoplasmic degeneration was significantly reduced compared with the model group. In addition, the dense substance thickened and the gap was narrowed. (3) The expression of BDNF-TrkB protein and gene in the electroacupuncture group increased significantly compared with that in the model group (P<0.05). The expression of BDNF-TrkB protein and gene in the model group decreased significantly compared with that in the blank group and the sham operation group respectively (P<0.01).Conclusion:Electroacupuncture Quchi (LI 11) -Yanglingquan (GB 34) regulate the expression of BDNF-TrkB gene and protein in hippocampus of the brain. High expression of the neurotrophic factor in hippocampus may promote the remodeling of synapses and improve the motor function of the central nervous system, thus achieving the relief of spasticity.